Sustainable Business Management - Van Riel, Karolien, ....-; Vanluchene, Sophie, ....-; De Malsche, Nils, 1992-; Fortie, Zoë, ....-; Segers, Karoline, 1994-; Maenhout, Freya, ....-; Verhulst, Joni, ....-; Vermandere, Floor, ....- (Gent : Owl Press, 2023)
Our world is changing fast. Global events are occurring more often and have a bigger impact on societies and economies than ever before. The current (business) environment shows that things have in order to guarantee meaningful lives for future generations. In the past, securing social and environmental stability was regarded as the sole responsibility of the government and non-profit organisations. Businesses, on the other hand, had only one objective: maximising shareholder value. However, due to the impact of businesses on social and environmental issues, governments and non-profit organisations can no longer deal with these problems by themselves. A shift towards sustainable business management has become a hot topic.If we want future business leaders to care more about sustainability when making decisions, we should introduce sustainable business management to students and ask them to reflect critically on the current situation and the possible solutions for our future. This book is meant to share the current state of affairs and give an extensive overview of relevant theories and ideas on sustainability, on an economic, social and environmental level. This book is an invitation for students and anyone who's interested to learn about sustainability, to get informed and share their thoughts with one another.
Docentenexemplaar
Keywords: Business management; Circular economy